Prevalence and Factors Associated with Stunting Among Children 0-59 Months in Rubirizi District-A Cross Sectional Study - Mubangizi Kizito; Noel Kansiime; Calvin Cherop; Fred Bagenda (Journal of Food Innovation, Nutrition, and Environmental Sciences)
Globally, 149 million children under five (21.9%) were stunted in 2018, with a higher burden in developing countries. In Uganda, 29% of children under five are stunted, but the prevalence in Rubirizi District is unknown. This study determined the prevalence and factors associated with stunting in Rubirizi District. A cross-sectional study involving quantitative and qualitative methods was conducted with 374 caregivers of children aged 0–59 months. Two focus group discussions were held with mothers and community leaders. Simple random sampling was used to select villages and caregivers. Data was collected using a structured questionnaire. Bivariate and multivariate logistic regression analyses were performed using Stata version 14. Variables with p < 0.05 were considered significant. Among the 374 children assessed, 85 (22.7%) were stunted. Significant factors associated with stunting included households with three children aged 0–59 months (aOR=3.78, 95%CI: 1.31-10.9, p=0.014), drinking water from unprotected well or spring (aOR=2.61, 95%CI: 1.20-5.68, p=0.015), children who never initiated breastfeeding within 1 hour (aOR=6.13, 95%CI: 2.78-13.5, p=0.001), children breasted up to 6 months (aOR=21.2, 95%CI: 3.76-120.1, p=0.014). This study underscores the need for caregivers to be sensitized to breastfeed for more than 12 months and educated on the benefits of exclusive breastfeeding.